Gender-Sensitive Post-Disaster Assessments - World Bank (Washington, DC, 2014)
This note on gender-sensitive post-disaster assessments is the eighth in a series of guidance notes on gender issues in disaster risk management (DRM) in the East Asia and the Pacific region. Targeting World Bank staff, clients and development partners, this note gives an overview of the main reasons for assessing gender impacts as part of a post-disaster needs assessment, identifies the key challenges, and recommends strategies and tools how to make post disaster assessments more gender-sensitive.